Abstracts Presented at the Conquering Heart Disease in the Himalayan Region International Conference 12-13 November 2010 - Editor, The (Nepalese Heart Journal, 2013)
Nepalese Heart Journal | Volume 7 | No.1 | November 2010 (special issue) | Page 54-78 DOI: http://dx.doi.org/10.3126/njh.v7i1.8505